Study on the Influence of Metal Ions on the Dispersion of Fine Calcium Gangue Minerals - Zhongyi Liu; Jie Liu; Yinfei Liao; Zilong Ma; Chenxi Jin (Molecules, 2022)
In this study, the calcium gangue material calcite (−10 μm) was used to investigate the effects of different kinds of metal ions and dosages on the dispersion behavior of calcite. The test results showed that the dispersion behavior of calcite was poor under strongly alkaline conditions without the addition of metal ions, and the reason for that was calcite dissolved ions. The degree of influence of different metal ions on calcite dispersion behavior was Fe3+ > Mg2+ > Na+. The three metal ion dosage tests showed that the dispersion behavior of calcite became poorer with the increase of metal ion dosage. This mainly showed that with the increase of Na+ dosage, the trend of the dispersion behavior of calcite was not obvious, but with the increase of Fe3+ and Mg2+ dosage, the trend of calcite dispersion behavior changed more. The dispersion behavior of calcite was devastated by 5 × 10−4 mol/L Fe3+ at pH = 4–12. The different mechanisms of the three metal ions were identified by zeta potential, solution chemistry, and XPS analysis. Na+ only changed the zeta potential value of the calcite surface, which acted as a compressed electric double layer. However, the formation of metal hydroxide species or metal hydroxide surface precipitation due to the adsorption of Fe3+ and Mg2+ on the mineral surface resulted in the change of the dispersion behavior of calcite.